Rationale and design of a multicenter, international and collaborative Coronary Artery Aneurysm Registry (CAAR). Issue 8 (24th March 2017) - Núñez‐Gil, Iván J.; Nombela‐Franco, Luis; Bagur, Rodrigo; Bollati, Mario; Cerrato, Enrico; Alfonso, Emilio; Liebetrau, Christoph; De la Torre Hernandez, José María; Camacho, Benjamín; Mila, Rafael; Amat‐Santos, Ignacio J.; Alfonso, Fernando; et al.
Abstract : Coronary artery aneurysm is defined as a coronary dilation that exceeds the diameter of adjacent segments or the diameter of the patient's largest normal coronary vessel by 1.5×. It is an uncommon disease that has been diagnosed with increasing frequency since the widespread appearance of coronary angiography. The published incidence varies from 1.5% to 5%, suggesting male dominance and a predilection for the right coronary artery. Although several causes have been described, atherosclerosis accounts for ≥50% of coronary aneurysms in adults. Reported complications include thrombosis and distal embolization, rupture, and vasospasm, causing ischemia, heart failure, or arrhythmias. The natural history and prognosis remain unknown, as definitive data are scarce. Controversies persist regarding the use of medical management (antithrombotic therapy) or interventional/surgical procedures. Only some case reports or small case series are available about this condition. The Coronary Artery Aneurysm Registry (CAAR;http://www.ClinicalTrials.gov NCT02563626) is a multicenter international ambispective registry that aims to provide insights on anatomic, epidemiologic, and clinical aspects of this substantially unknown entity. In addition, the registry will assess management strategies (conservative, interventional, or surgical) and their short‐ and long‐term results in a large cohort of patients. Clinical Trial registration:ClinicalTrials.gov . Unique identifier: NCT02563626.